1995
DOI: 10.1016/0954-6111(95)90069-1
|View full text |Cite
|
Sign up to set email alerts
|

Late pulmonary sequela following burns: persistence of hyperprocalcitonemia using a 1–57 amino acid N-terminal flanking peptide assay

Abstract: Seven patients were evaluated at a mean duration of 8.4 yr after sustaining inhalational injury associated with burns. At the time of re-examination, the patients were asymptomatic and had normal chest X-rays, and arterial blood gases. Three of the seven patients had abnormally elevated serum calcitonin levels. The spirometry (FEV1) measurements showed an inverse trend to that of the serum calcitonin levels. The elevated calcitonin levels had an abnormal predominance of the procalcitonin component as assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Other than infection, PCT levels increase in premature infants, hypoxia, RDS, and hemodynamic instability, decreasing its specificity in early-onset sepsis10,11,12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other than infection, PCT levels increase in premature infants, hypoxia, RDS, and hemodynamic instability, decreasing its specificity in early-onset sepsis10,11,12).…”
Section: Discussionmentioning
confidence: 99%
“…Research studies reported that PCT is more effective than CRP at follow-up, as PCT levels rise earlier and return to normal levels more rapidly than CRP levels2,3,4,5,6,7,8,9). However, some studies have shown a decrease in PCT specificity associated with an increase in uninfected preterm babies, hypoxia, neonatal respiratory distress syndrome (RDS), and hematologic failure10,11,12). Furthermore, one report suggested that PCT is only significant when used in combination with other tests, and it is not appropriate for diagnosing sepsis13).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is no available assay that detects ProCT exclusively. Initially, for the purpose of studying systemic infection, inflammation and sepsis, a very sensitive, single‐antibody assay of NProCT was developed for research purposes (Nylén et al. , 1995; Snider et al.…”
Section: Proctmentioning
confidence: 99%
“…For the measurement of calcitonin precursors, we used a sensitive radioimmunoassay that utilizes an antiserum to the amino portion of the prohormone. It detects both aminoprocalcitonin and the intact procalcitonin molecule [11,13,28]. This assay has the advantage of a sensitivity of 0´65 pmol L À1 , and detects values in nearly all normal persons (reference range: 2±12 pmol L À1 ).…”
Section: Laboratory Measurementsmentioning
confidence: 99%